Design of the Hospital Integrated Information Management System Based on Cloud Platform - Aijing, L (West Indian Med J, 2015)
At present, the outdated information management style cannot meet the needs of hospital management, and has become the bottleneck of hospital's management and development. In order to improve the integrated management of information, hospitals have increased their investment in integrated information management systems. On account of the lack of reasonable and scientific design, some hospital integrated information management systems have common problems, such as unfriendly interface, poor portability and maintainability, low security and efficiency, lack of interactivity and information sharing. To solve the problem, this paper carries out the research and design of a hospital information management system based on cloud platform, which can realize the optimized integration of hospital information resources and save money.